Influence of different reinforcements on properties of metal matrix composites: A review. (2021) - Anandaraj, T.; Sethusundaram, P.P.; Chanakyan, C.; Sakthivelu, S.; Meignanamoorthy, M.
Abstract: Metal matrix composites (MMCs) possess excellent properties than that of other materials. Owing to this merits MMCs are extensively used for various engineering applications. In general metal has better properties in addition to that when it is reinforced with some particulates extraordinary properties can be achieved. This review article put forth an attempt to display the influence of different reinforcements on properties of metal matrix composites. The applications of MMCs in various engineering fields are also has been explained in detail.